2011
DOI: 10.5433/1679-0359.2011v32n3p909
|View full text |Cite
|
Sign up to set email alerts
|

Épocas de poda na sazonalidade, produção e qualidade dos frutos da goiabeira 'Paluma'

Abstract: Foram avaliadas a produção e a qualidade dos frutos de goiabeiras 'Paluma' quando submetidas à poda de frutificação nos meses de junho e julho/2007, em Botucatu-SP. Para tanto, avaliaram-se o número de frutos por planta, massa e diâmetros longitudinal e transversal dos frutos, produção por planta, produtividade, sólidos solúveis (SS), acidez titulável (AT), pH, 'ratio' (SS/AT), teor de ácido ascórbico e açúcares redutores totais (ART). O delineamento experimental foi o inteiramente casualizado, constituído por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 9 publications
0
13
1
7
Order By: Relevance
“…In São Manuel (another municipality in S.P. ), Paluma trees pruned in September and October had a lower output than trees pruned in August (Ramos et al, 2011). In contrast, Serrano et al (2008), in Pinheiro, state of Espírito Santo, observed greater Paluma fruit output in December-pruned trees (in addition to greater fruit weight), compared to February pruning.…”
Section: Resultsmentioning
confidence: 92%
“…In São Manuel (another municipality in S.P. ), Paluma trees pruned in September and October had a lower output than trees pruned in August (Ramos et al, 2011). In contrast, Serrano et al (2008), in Pinheiro, state of Espírito Santo, observed greater Paluma fruit output in December-pruned trees (in addition to greater fruit weight), compared to February pruning.…”
Section: Resultsmentioning
confidence: 92%
“…A relação SS/AT (ratio) é um dos índices mais utilizados para determinar a maturação e a palatabilidade dos frutos, pois é um indicativo do sabor (RAMOS et al, 2011). Esta relação foi influenciada pelo estádio de maturação, uma vez que os frutos colhidos nos estádios iniciais foram os que apresentaram, ao final do período de amadurecimento, os menores valores de ratio (Figura 1), sugerindo sabor menos agradável, o que também foi relatado por Azzolini et al (2004a, b) em goiabas 'Paluma' e 'Pedro Sato'.…”
Section: Ponto De Colheita E Qualidade De Goiabasunclassified
“…Soluble and total pectins were extracted in 95% ethanol according to the procedures described in McReady The extraction of phenolic compounds was carried out according to the method described in Swain and Hillis (1959) having as extractant methanol at 99.5% (v/v) for dimers, methanol at 50% (v/v) for oligomers and distilled water for the polymeric forms. To determine the phenolic contents the methodology described in Reicher et al (1981) was applied and the results expressed in mg/100 g fresh tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Menezes et al (2015) similarly did determine an increase in the ratio SS/ TA of red pitayas during ripening. The SS/TA ratio is one of the most used indices to determine ripening and palatability of fruit because it is an indication of tastiness (Ramos et al, 2011).…”
Section: Quality and Ripening Variablesmentioning
confidence: 99%